Model archiving and sustainment for aerospace design - Barker, Sean (Engineer) (SAE International, 2020)
Model Archiving and Sustainment for Aerospace Design, written by Sean Barker, an industry veteran from the UK, focuses on the techniques developed by the LOTAR (Long Term Archiving and Retrieval) project, a collaboration among the major US and European aerospace companies. Long-term archiving models follows LOTAR by taking the exchange of mechanical CAD file as the paradigm for long-term retention and developing general principles for model archiving. These include electrical systems, composite parts, systems engineering and requirements engineering. The increasing availability of model-based software has made the problems of long-term model sustainment more visible and pressing for a solution. Industries following LOTAR today include aerospace, automotive, nuclear and ship building. In the aerospace sector, the challenges are even bigger. Model Archiving and Sustainment for Aerospace Design makes sense of the immense challenges of rapid software change to ensure that the aircraft can be profitably sustained for the next seventy years.